Approach to 3-(Cyclo)alkylpiperidines through ‘sp3–sp3 via sp2–sp3’ Coupling - Subota, Andrii I.; Grygorenko, Oleksandr O.; Valter, Yevheniia B.; Tairov, Maxim A.; Artamonov, Oleksiy S.; Volochnyuk, Dmitriy M.; Ryabukhin, Sergey V. (Synlett, 2015)
The idea of introducing (cyclo)alkyl substituents at the C-3 atom of the piperidine ring, that is, formal sp3–sp3 retrosynthetic disconnection, is implemented through a two-step reaction sequence including directed ortho metalation of a pyridine derivative and the subsequent quenching with a carbonyl compound, followed by catalytic hydrogenation. This robust but very efficient method allows for multigram preparation of sp3-rich 3-(cyclo)alkylpiperidines, which are valuable building blocks for medicinal chemistry and other areas.
Keywords: heteroaliphatic compounds; alicyclic compounds; lead-oriented synthesis; catalytic hydrogenation; piperidines